Multiple Temptations - Stovall, John E. (Econometrica, 2010)
We use a preference-over-menus framework to model a decision maker who is affected by multiple temptations. Our two main axioms on preference—exclusion and inclusion—identify when the agent would want to restrict his choice set and when he would want to expand his choice set. An agent who is tempted would want to restrict his choice set by excluding the normatively worst alternative of that choice set. Simultaneously, he would want to expand his choice set by including a normatively superior alternative. Our representation identifies the agent's normative preference and temptations, and suggests the agent is uncertain which of these temptations will affect him. We provide examples to illustrate how our model improves on those of Gul and Pesendorfer (2001) and Dekel, Lipman, and Rustichini (2009).